2014
DOI: 10.1021/ic501146r
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Magneto-optical Bacteria

Abstract: Abstract. "Two-in-one" magneto-optical bacteria have been produced using the probiotic Lactobacillus fermentum ® for the first time. We took advantage of two features of bacteria to synthesize this novel and bifunctional nanostructure: their metal-reducing properties, to produce gold nanoparticles, and their capacity to incorporate maghemite nanoparticles at their external surface. The magnetooptical bacteria survive the process and behave as magnets at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Chemical structure of p-hydroxyphenyllactic acid HPLA. , which are quite reduced in the presence of L. fermentum (Carmona, Martin, Galvez, & Dominguez-Vera, 2014;González, Gálvez, Clemente-León, & Domínguez-Vera, 2015). This result indicates that the chemical reducing mechanism of L. fermentum does not solely contain HPLA but also other reducing molecules.…”
Section: Lactobacillus Fermentum Shows a High Ferric-reducing Activitymentioning
confidence: 77%
“…Chemical structure of p-hydroxyphenyllactic acid HPLA. , which are quite reduced in the presence of L. fermentum (Carmona, Martin, Galvez, & Dominguez-Vera, 2014;González, Gálvez, Clemente-León, & Domínguez-Vera, 2015). This result indicates that the chemical reducing mechanism of L. fermentum does not solely contain HPLA but also other reducing molecules.…”
Section: Lactobacillus Fermentum Shows a High Ferric-reducing Activitymentioning
confidence: 77%
“…In another study by Carmona et al magneto-optical bacteria were produced using probiotic Lactobacillus fermentum [ 43 ]. By exploiting metal-reduction properties (to produce gold nanoparticles) and their capacity to incorporate iron oxide nanoparticles at their external surface, they reported living magneto-optical bacteria behaving as a magnet at room temperature.…”
Section: Bacteria and Yeastmentioning
confidence: 99%
“…We have previously demonstrated that iron oxide and gold nanoparticles can be incorporated within the exopolysaccharide matrix (EPS) of some probiotic bacteria leading to live, hybrid probiotic-NPs materials [15,16]. EPS are natural polysaccharides secreted by some bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis of metallic nanoparticles using microorganisms as reducing agents has gained popularity in recent decades as it presents several advantages over traditional synthetic methods [22,23]. There are other microorganisms with this reducing capacity, including several probiotic bacteria such as Lactobacillus fermentum [16].…”
Section: Introductionmentioning
confidence: 99%